The theory and the practice of market law in medieval Islam a study of Kitāb Niṣāb al-Iḥtisāb of ʻUmar b. Muḥammad al-Sunāmī (fl. 7th-8th/13th-14th century) - ʻIzz al-Dīn, Mūʾil Yūsuf (E.J.W. Gibb Memorial Trust, 1997)
This book represents an explanation of the institution of hisba in medieval Islam, through one of the most used texts in the field. It includes a thorough translation of the text, written by a practising muhtasib, scholar and judge, together with accompanying biographical and bibliographical notes.